2013
DOI: 10.1093/jxb/ert098
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of evolution at the gametophytic self-incompatibility Sorbus aucuparia (Pyrinae) S pollen genes support the non-self recognition by multiple factors model

Abstract: S-RNase-based gametophytic self-incompatibility evolved once before the split of the Asteridae and Rosidae. In Prunus (tribe Amygdaloideae of Rosaceae), the self-incompatibility S-pollen is a single F-box gene that presents the expected evolutionary signatures. In Malus and Pyrus (subtribe Pyrinae of Rosaceae), however, clusters of F-box genes (called SFBBs) have been described that are expressed in pollen only and are linked to the S-RNase gene. Although polymorphic, SFBB genes present levels of diversity low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Mutant analyses indicated SFBB1 of the Pyrus pyrifolia S 4 haplotype is required for pollen tube growth in a pistil producing S 1 -RNase, indicating multiple SFBB genes, including SFBB1, confer cross-compatibility (Kakui et al, 2011;Okada et al, 2008;Saito et al, 2012). Although only two or three types of SFBB were reported when they were initially discovered, at least 8, 11, and 16 types have subsequently been identified in the genera Pyrus, Malus, and Sorbus, respectively (Aguiar et al, 2013;Kakui et al, 2011;Okada et al, 2013;Sassa et al, 2007). Furthermore, in contrast to the low sequence polymorphism observed among alleles of the same type of SFBB, synonymous and non-synonymous substitution rates among different types of SFBB were comparable to those among different S-RNase alleles (Kakui et al, 2011).…”
Section: Collaboration Of Multiple F-box Genes To Determine Specificimentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant analyses indicated SFBB1 of the Pyrus pyrifolia S 4 haplotype is required for pollen tube growth in a pistil producing S 1 -RNase, indicating multiple SFBB genes, including SFBB1, confer cross-compatibility (Kakui et al, 2011;Okada et al, 2008;Saito et al, 2012). Although only two or three types of SFBB were reported when they were initially discovered, at least 8, 11, and 16 types have subsequently been identified in the genera Pyrus, Malus, and Sorbus, respectively (Aguiar et al, 2013;Kakui et al, 2011;Okada et al, 2013;Sassa et al, 2007). Furthermore, in contrast to the low sequence polymorphism observed among alleles of the same type of SFBB, synonymous and non-synonymous substitution rates among different types of SFBB were comparable to those among different S-RNase alleles (Kakui et al, 2011).…”
Section: Collaboration Of Multiple F-box Genes To Determine Specificimentioning
confidence: 99%
“…This suggests the diversification of SI specificity was due to the duplication and differentiation of the SFBB loci as well as the diversification of SRNase alleles. Aguiar et al (2013) reported that the most closely related Sorbus SFBB genes diverged 8.27 million years ago (MYA). The most distantly related SFBB genes diverged 23.96 MYA, which is similar to the age of the oldest Maleae S-RNase specificity lineage (approximately 23 million years old; Vieira et al, 2010).…”
Section: Collaboration Of Multiple F-box Genes To Determine Specificimentioning
confidence: 99%
“…At the S -locus region, the S-RNase gene is always surrounded by the S -pollen gene(s), that can be one gene as in Prunus (called SFB ; [ 32 - 37 ], or multiple genes as in Pyrinae (called SFBB s; [ 38 - 41 , 45 , 47 ], and Solanaceae (called SLF s [ 14 , 46 , 47 ]). It should be noted that in Prunus , other F-box genes called SLFL s, not involved in GSI specificity determination [ 69 ] are also found surrounding the S-RNase gene [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pollen component(s), always an F-box protein, has been identified as one gene in Prunus (Rosaceae; the gene is called SFB [ 32 - 37 ]), but multiple genes in Pyrinae (Rosaceae; the genes are called SFBB s [ 38 - 45 ]) and Solanaceae (called SLFs ; [ 46 - 48 ]). F-box genes belong to a large gene family, and so far, no typical amino acid patterns have been reported for S -locus F-box protein sequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation